Apa determinan tingkat pengungkapan Islamic Social Reporting bank umum syariah Indonesia? - Ruri Deviani; Hadri Kusuma (Jurnal Ekonomi & Keuangan Islam, 2019)
The inconsistent result of previous studies on the effect of Islamic corporate governance, good corporate governance, profitability, liquidity, and the age of the company may be due to the use of different indicators. This study aims to analyze factors influencing the disclosure index of Islamic Social Reporting (ISR) general Islamic banks for the period of 2014-2017. The research sample was 48 firm-year observations from 12 banks. The statistical tool used to test the hypothesis is using Autoregressive Conditional Heteroskedasticity (ARCH) with the help of Eviews software version 9. The results of this study indicated that the Islamic Corporate Governance and age of the banks are the determinants of the ISR while Good Corporate Governance, Liquidity and profitability variables have no effect on the ISR disclosure.